Los factores socioambientales y la generación de puntos críticos de acumulación de residuos sólidos en el distrito de Trujillo, Perú (2023) - Guerra-Blas, Deysi Paola (2025)
The district of Trujillo faces a public health issue due to the emergence of critical points of solid waste accumulation, which increases the risk of disease transmission, degrades the urban environment, and negatively affects the population’s perception of safety and well-being. The objective of this study is to analyze the spatial patterns of critical point generation in Trujillo and their relationship with socio-environmental factors that may explain their distribution. A quantitative approach was employed, specifically a descriptive-correlational, non-experimental design, combining remote sensing techniques, spatial analysis through Geographic Information Systems (GIS), and fieldwork based on household surveys. The study targeted residents over 18 years of age in the district of Trujillo, whose households were located within a 30-meter radius of the identified critical points. A total of 100 surveys were conducted to assess environmental awareness and the imitation of inadequate waste disposal practices at the household level. For the spatial analysis, tools such as QGIS and Google Earth Engine were used to obtain geospatial data regarding the location of markets, green areas, and vacant land. The results showed that non-recoverable inorganic waste accounted for 58.2% of the identified critical points, followed by organic waste (35.4%), which was mainly concentrated in the eastern area of the district. Spearman’s correlation revealed significant relationships between the presence of markets, restaurants, and vacant land and the accumulation of organic and inorganic waste. Moreover, it was observed that areas with lower levels of environmental awareness were associated with a higher concentration of solid waste, highlighting the importance of environmental education in reducing critical points.